Automation of the process development special content - Міхєєв, Ю.І.; Барабаш, А.О. (Science-based technologies, 2018)
The work analyzes the peculiarities of the implementation of psychological influence through means of Mass media. The described main principles and recommendations for the development of special content on the basis of a news audiovisual message based on methods of practical determination of the influence of messages on subconsciousness of strata and man, namely: phonetic analysis on the basis of the formation of a semantic differential in the application to the sounds of language; a linguistic analysis of the positive and destructive influence of individual words on the meaningfulness of the text in its entirety; color-sound analysis; neurolinguistic programming to determine the load on the main sensory channels of human perception. Analysis of the corresponding phonetic meanings of words using the semantic differential allows to adjust the orientation of special content texts and to assess the degree of the target audience readiness to effective perception of information with latent psychological influence. The order of the target audience analysis as one of the main stages during the special content development is given. The structural scheme of the automation algorithm for the development of special content for a specific target audience is provided, which involves performing stages from: the target audience definition and clarification; the determining of target audience effectiveness; determining the causes and consequences existing behavior of target audience; the identify vulnerabilities target audience; determining the receptivity of target audience; determining the availability of target audience; development of arguments and recommendations; clarification of the primary criteria for assessing the target audience. In accordance with the given algorithm, specialized software was developed, the final result of which is the concept of special content.